High Reflectivity Compounds of Cadmium Sulfide/Magnesium Fluoride Distribution Bragg Reflectors: Design, Simulation, and Comparative Analysis - Swara, Jihad A.; Chaqmaqchee, Faten A.; Sediq, Khalid N. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
This work investigates the optical performance of a distributed Bragg reflectors (DBRs) structure, designed with a Matlab program using inorganic compounds of cadmium sulfide (CdS) and magnesium fluoride (MgF2 ) with a central operational wavelength of 650 nm. Because CdS (high index) and MgF2 (low index) have very different refractive indices, the proposed DBR can reflect light effectively using fewer alternating layers. The Transfer Matrix Method simulation method indicates that the DBR structure reaches its maximum reflectivity with just six-layer pairs, emphasizing its optical efficiency and structural simplicity. A comparative analysis with other DBR structures demonstrates the superior performance of CdS/MgF2 DBR, which exhibits a broader usable stopband at around 181.82 nm, the highest bandwidth of 298.49 nm, and a relatively moderate Q-factor (2.18), indicative of an enhanced reflector response. These results establish CdS/MgF2 DBR as highly efficient reflectors that are well-suited for optical systems functioning in the visible spectrum.